Indications of Sentinel Node Biopsy in Thin Melanoma - Silva,Fernanda Braga (2010)
ABSTRACT Objective: To assess data on survival, recurrence and histological factors in positive and negative sentinel lymph nodes in thin melanoma cases. Methods: A systematic review was conducted on observational studies in four databases (Cochrane Library, Medline, Embase and Lilacs). Positive and negative micrometastases in sentinel lymph node biopsy were compared regarding the clinical outcomes – death and recurrence – and six histological factors – vertical growth phase, Breslow thickness, Clark level, ulceration, regression and mitosis rate. Results: Positive sentinel lymph node is statistically associated with greater risk of death in six studies (OR: 7.2; 95%CI [2.37-21.83]; I2 0%) and also to recurrence in three studies (OR: 30.7; 95%CI [12.58-74.92]; I2 36%). Comparing positive and negative groups, the histological factors predicting positive sentinel nodes and poor prognosis were: mitosis rate ≥ 5/mm2 (OR: 16.29; 95%CI [3.64-72.84]; I2 40%); VGP (OR: 2.93; 95%CI [1.08-7.93]; I2 59%); Breslow thickness ≥ 0.75mm (OR: 2.23; 95%CI [1.29-3.86]; I2 0%); and Clark level IV-V (OR: 1.61; 95%CI [1.06-2.44]; I2 34%). Conclusions: The statistically significant results associated with the presence of micrometastases in thin melanomas were Breslow thickness ≥ 0.75 mm, Clark level IV-V and mitoses ≥ 5/mm2, absence of regression. This histological factor of ulceration was associated, but not statistically significant.